Recycling lake sediment to agriculture: Effects on plant growth, nutrient availability, and leaching - Kiani, Mina; Raave, Henn; Simojoki, Asko; Tammeorg, Olga; Tammeorg, Priit (The Science of the total environment, 2021)
Sediment removal from eutrophicated shallow lakes may not only be an effective method for lake restoration but also provides the potential for recycling nutrients from sediments to crop production. However, finding a suitable strategy for sustainably reusing the sediment remains a challenge. Therefore, current study focused on the best practices in applying the sediment from a shallow eutrophicated lake to the soil in terms of grass yield, nutrient uptake, and nutrient leaching. During a nine-month lysimeter experiment, 100-cm high columns were filled with six combinations of soil, sediment, and biochar, with or without meat bone meal organic fertilizer. Aboveground biomass, root mass distribution in soil, nutrient concentration, phosphorus (P) uptake of perennial ryegrass (Lolium perenne L.) along with easily soluble nutrients in the growing medium, and leached mineral nitrogen (N) and P levels were measured. Plant growth conditions were improved by sediment additions, as the yield and P uptake of ryegrass nearly doubled in treatments containing sediment compared to the control soil. While the sediment was richer in macro and micronutrients (e.g. P and N) compared to the soil, the leached N and P levels from both treatments were almost equivalent (N < 830 mg m−2 and P < 3 mg m−2). In addition, applying a 2-cm layer of biochar between the sediment and soil reduced P and N leaching by 50%. According to the results, applying a 75-cm thick layer of sediments on agricultural sandy loam soils surrounding the lake seems a promising practice for improving plant yield and soil nutrient status without increasing of P and N leaching from soil. [Display omitted] •We tested excavated lake sediment as growing media for plants.•The sediment treatments increased growth and P uptake of ryegrass.•Al and Fe bound P was the only fraction positively correlating with plant P uptake.•An Fe:P ratio lower than 15 in sediment may explain the high bioavailability of P.•Biochar layer is a promising addition for reducing P and N leaching from sediment.